Modus Operandi dan Perlindungan Hukum Anak Korban Eksploitasi Ekonomi oleh Orang Tua Berdasarkan Putusan Pengadilan Ditinjau dari Tujuan Pemidanaan - Tiara Medha Maharani; Wahyu Priyanka Nata Permana (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Economic exploitation by parents towards their children is increasing. Parents who have an obligation to protect their children actually make children victims for their own benefit. This study discusses the modus operandi and legal protection of children who are victims of economic exploitation by parents based on court decisions. This study will examine the Decision of the Semarang District Court No. 8/Pid.Sus/2014/PN.Smg and the Decision of the Kuala Kapuas District Court No. 235/Pid.Sus/PN.Klk. The legal research method used is normative with a statutory approach, a conceptual approach, and a case approach. The results of the study, first, the modus operandi in the Decision of the Semarang District Court No. 8/Pid.Sus/2014/PN.Smg parents exploit and manipulate their children to get shares while in the Decision of the Kuala Kapuas District Court No. 235/Pid.Sus/PN.Klk. parents make children as Commercial Sex Workers (CSW). Second, legal protection is reviewed from the purpose of punishment based on court decisions against children as victims that the Decision at the Semarang District Court No. 8/Pid.Sus/2014/PN.Smg is related to the Theory of Relative Punishment Purposes while the Decision at the Kuala Kapuas District Court No. 235/Pid.Sus/PN.Klk is related to the Theory of Combined Punishment Purposes.